Successful subtotal gastrectomy and hepatectomy for HER2-positive gastric cancer with liver metastasis after trastuzumab-based chemotherapy: a case report - Yuki Hirase; Takaaki Arigami; Yota Kawasaki; Daisuke Matsushita; Masataka Shimonosono; Yusuke Tsuruda; Ken Sasaki; Yoichi Yamasaki; Takahiko Hagihara; Hidetoshi Noma; Michiyo Higashi; Hiroshi Kurahara; et al. (Surgical Case Reports)
Abstract Background Conversion surgery (CS) after chemotherapy is weakly recommended as a promising tool for improving prognoses in patients with unresectable gastric cancer. Moreover, several investigators have demonstrated the clinical efficacy of subtotal gastrectomy (sTG) with a small remnant stomach for the nutritional status and surgical outcome compared with total gastrectomy. Here, we report a patient with liver metastasis from human epidermal growth factor receptor 2 (HER2)-positive gastric cancer who underwent sTG and hepatectomy after trastuzumab-based chemotherapy. Case presentation An 84-year-old male patient was diagnosed with HER2-positive gastric cancer with a single liver metastasis. He was treated with eight courses of trastuzumab in combination with S-1 and oxaliplatin as first-line chemotherapy. The primary tumor and liver metastasis shrank significantly. The metastatic liver lesion’s reduction rate was 65%. According to the Response Evaluation Criteria in Solid Tumors, the patient had a partial response. Therefore, he underwent an sTG with D2 lymphadenectomy and partial hepatectomy of segment 2. Histopathological examination revealed a grade 3 histological response without lymph node metastases from the primary tumor. No viable cancer cells were observed in the resected liver specimens. The patient received adjuvant chemotherapy with S-1. The postoperative quality of life (QOL) evaluated using the Postgastrectomy Syndrome Assessment Scale-45 was maintained, and the patient was still alive 8 months after the CS without recurrence. Conclusions An sTG with a small remnant stomach might be clinically useful for preventing a decline in QOL and improving prognoses in patients with stage IV gastric cancer after chemotherapy.